An Italian Renaissance sextet : six tales in historical context - Baca, Murtha; Martines, Lauro (Lorenzo da Ponte Italian library series., 2004)
"This collection of six tales offers enticing views into the history of Renaissance Italy, with fiction and fictional modes becoming gateways to a real, historical world. All written between 1400 and 1500 - among them a rare gem by Lorenzo the Magnificent and a famous account featuring Filippo Brunelleschi - the stories are presented here in lively translations ... The tales deal with marriage, deception, rural manners, gender relations, social ambitions, adultery, homosexuality, and the demands of individual identity. Each is accompanied by an essay in which Lauro Martines situates the story in its temporal context, transforming it into an outright historical document"--BOOK JACKET.